Millennials’ adoption of omnichannel retailing - Chong, Alain Yee Loong (University of Nottingham Ningbo China, 2018)
This study examines Millennials’ adoption of omnichannel retailing and the underlying mechanism. Four studies were conducted to examine the moderating roles of product category and regulatory focus on Millennial’s purchase intentions in omnichannel retailing. Study 1 and 2 findings show that Millennials adopt omnichannel retailing over pure brick-and-mortar and pure online retailing and that perceived convenience, enjoyment, and value determine the adoption of omnichannel retailing for shopping. Study 3 shows that product category influences Millennial’s preference for omnichannel retailing. Finally, Study 4 offers support for the moderating role of Millennials’ regulatory focus in determining their retail format choice for shopping.